Inflation versus price-level targeting and the zero lower bound: Stochastic simulations from the Smets-Wouters US model - Michael C. Hatcher (Cardiff University, Cardiff Business School, 2011)
Using a version of the Smets-Wouters model of the US economy augmented to include both New Keynesian and New Classical sectors, this paper investigates the performance of inflation targeting and price-level targeting when the zero lower bound on nominal interest rates is occasionally-binding. Several notable results emerge. First, the unconditional probability of hitting the lower bound is lower under price-level targeting than inflation targeting, with 'lower bound episodes' being less frequent and lasting for shorter periods of time. Second, the volatilities of key macroeconomic variables are lower under price-level targeting than inflation targeting. Third, the lower frequency and severity of lower bound episodes under price-level targeting appears to have a first-order impact on consumption, investment and output, raising their mean values. Intuitively, price-level targeting performs well because inflation expectations act as automatic stabilisers, reducing the chance of hitting or remaining at the lower bound whilst also providing stability when the economy is away from the lower bound.
Keywords: E52; E58; 330; zero lower bound; occasionally-binding constraint; price-level targeting; inflation targeting; Inflationsrate; Inflation Targeting; Preisniveau; Inflationserwartung; Zinspolitik; Theorie